Legal Certainty on Prohibition of Transfer of Debtor's Rights and Obligations in Fiduciary Security Agreement - Yanto, Marga; Juwita, Juwita (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the legal certainty regarding the prohibition of the transfer of debtors' rights and obligations in fiduciary guarantee agreements based on Article 36 of Law Number 42 of 1999. The research employs a normative legal method with a qualitative approach through case studies and analysis of court decisions. The results indicate that although the prohibition of transfer is explicitly regulated by law, its implementation still faces various challenges, primarily due to weak law enforcement, inconsistent application of sanctions, and the prevalence of violations that are not strictly addressed. The findings reveal that the practice of transferring fiduciary objects without creditor consent remains widespread, creating legal uncertainty and risks of loss for the parties involved. Based on an analysis of Gustav Radbruch's theory of legal certainty, Philipus M. Hadjon's theory of legal protection, and John Rawls' theory of justice, this study recommends the need for legal reform of fiduciary guarantees through digitization of the registration system, strengthening of monitoring mechanisms, inter-agency synergy, and improving public legal literacy. These reforms are expected to enhance legal certainty, the effectiveness of creditor protection, justice for debtors, and the protection of bona fide third parties proportionally in the fiduciary-based financing system in Indonesia.